Reconfigured securityscapes in Louis Trichardt: Possibilities, limitations, and contradictions - Chakwizira, James (Frontiers in Sustainable Cities, 2023)
Insecurity, violence, and xenophobia manifest at different geographic scales of the South African landscape threatening to compromise, reverse, derail, and contradict the envisaged democratic processes and gains in the country. Since the dawn of the new democracy in 1994, the South African landscape has witnessed surges of different scales of violence, protests, riots, looting, criminality, and vigilantism in which question marks have been raised with respect to the right to the city or urban space and the right to national resources and opportunities, i.e., access, use, distribution and spread of social, economic, environmental, and political resources and benefits. Louis Trichardt is a small rural agricultural town located in the Makhado municipality of Vhembe District in Limpopo Province, South Africa. In the study, this town is used as a securityscapes lens of analysis to explore urban conflict and violence. The relative importance index (RII) was used to measure the barriers and solutions to advance safe neighborhoods' settlements and built environment areas in the study area. In this way, issues influencing the performance of reconfigured securityscapes in Louis Trichardt were explored by highlighting how new town neighborhood securityscape initiatives and activities are contributing to space, place, and culture change management transitions. The discussion pressure and pain points revolve around the widening societal inequalities, deepening poverty, influx of (ll)legal migrants and migrant labor, lingering xenophobia, and failure to embrace the otherness difficulties in the country. Findings highlight the options for urban (in)security, social (in)justice, and (re)design in post-colonies possibilities, limitations, and contradictions of securityscapes in (re)configured spaces of Louis Trichardt. Policy and planning proposals to improve safety and security spatial logic and innovation are explored. The critical role of community and local neighborhood watch groups in complementing state security and private registered security systems is one way of tackling this matter.